2005
DOI: 10.1073/pnas.0506461102
|View full text |Cite
|
Sign up to set email alerts
|

Use of RNA interference inDrosophilaS2 cells to identify host pathways controlling compartmentalization of an intracellular pathogen

Abstract: Three genome-wide RNA interference screens were performed in Drosophila S2 cells to dissect the contribution of host processes to Listeria monocytogenes entry, vacuolar escape, and intracellular growth. Among the 116 genes identified, several host pathways previously unrecognized as playing a role in listerial pathogenesis were identified: knockdowns affecting vacuolar trafficking to and from the multivesicular body bypassed the requirement for the essential pore-forming toxin listeriolysin O in mediating esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 40 publications
1
111
0
Order By: Relevance
“…While the ESCRT machinery restricts the growth of M. smegmatis, genome-wide screens in Drosophila found that CG8055, Vps28, and Vps4 were required for intracellular growth of Listeria monocytogenes (8,9), suggesting that diminished ESCRT activity does not make cells generally susceptible to bacterial infection. However, when these cells were infected with a mutant strain of L. monocytogenes that normally gets trapped in the vacuole because of a defect in the cytolysin, which is required for escape from the phagosome (LLO), the bacteria were better able to escape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the ESCRT machinery restricts the growth of M. smegmatis, genome-wide screens in Drosophila found that CG8055, Vps28, and Vps4 were required for intracellular growth of Listeria monocytogenes (8,9), suggesting that diminished ESCRT activity does not make cells generally susceptible to bacterial infection. However, when these cells were infected with a mutant strain of L. monocytogenes that normally gets trapped in the vacuole because of a defect in the cytolysin, which is required for escape from the phagosome (LLO), the bacteria were better able to escape.…”
Section: Discussionmentioning
confidence: 99%
“…Arguing against this possibility, phagosomal escape of LLO-minus Listeria requires the bacterial phospholipases. Thus, loss of phagosome integrity in ESCRT-depleted cells still depends on bacterial factors (9). Furthermore, we examined by electron microscopy the intracellular location of M. smegmatis in S2 cells that had been depleted of Tsg101 (SI Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria lacking LLO are also unable to escape the phagosome during infections of S2 cells in vitro (Cheng and Portnoy, 2003). The Portnoy group not only characterized known aspects of LLO function, but also then performed a large-scale RNAi screen to alter the course of a Listeria infection of cultured Drosophila cells (Cheng et al, 2005). By comparing the effects of different RNAis on wild-type bacteria and mutants in LLO, they identified several fly genes specifically involved in LLO pathogenesis.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Theoretical arguments aside, however, many non-physiological microbes cause unexpectedly interesting infections in the fly. Some particularly odd examples include: Listeria monocytogenes (which has elegant temperature regulation of virulence and might not be expected to be virulent at less than 30°C), Streptococcus pneumoniae (a common inhabitant of our airways that has to be grown under CO 2 and probably never encounters the fly), and Chlamydia trachomatis (a highly co-evolved obligate intracellular pathogen) (Cheng and Portnoy, 2003;Mansfield et al, 2003;Agaisse et al, 2005;Cheng et al, 2005;Elwell and Engel, 2005;Pham et al, 2007).…”
Section: Virulence Factorsmentioning
confidence: 99%